Do migrants take the jobs of native workers? - Amelie F. Constant (IZA World of Labor, 2014)
Neither public opinion nor evidence-based research supports the claim of some politicias and the media that immigrants take the jobs of native-born workers. Public opinion polls in six migrant-destination countries after the 2008–2009 recession show that most people believe that immigrants fill job vacancies and many believe that they create jobs and do not take jobs from native workers. This view is corroborated by evidence-based research showing that immigrants—of all skill levels—do not significantly affect native employment in the short term and boost employment in the long term.
Keywords: J1; J2; J6; 330; employment; job creation; native workers; job upgrading; immigration impact; economic complementarity; competition